Development of key technologies for audio retrieval and vocal teaching system based on sensor networks - Li Shu (Measurement: Sensors, 2024)
Traditional audio processing technology often faces the challenge of efficiency and accuracy in the face of large-scale audio data and complex sound content. The purpose of this study is to develop the key technology of audio retrieval and vocal music teaching system based on sensor network, aiming at the rich audio data and real-time monitoring function provided by sensor network. The sensors suitable for audio retrieval and vocal music teaching were selected and rationally arranged in the designated position to obtain accurate and comprehensive audio data. The algorithm is also optimized and improved to improve the performance and stability of the system. The accuracy and efficiency of audio retrieval can be effectively improved by using sensor networks. The vocal music teaching system based on sensor networks can provide comprehensive and accurate sound evaluation and guidance. Good results have been obtained in the practical application of this method, which proves its feasibility and effectiveness in the field of audio retrieval and vocal music teaching.